The decorative images' seductive effect in e-learning depends on attentional inhibition - González, Federico M. (2019)
Two studies sought to replicate and extend the seductive effect of decorative pictures in expository text comprehension to an e-learning environment. In the first study, undergraduate students read and answered questions about two texts, with and without decorative, irrelevant images, in an e-learning course. The presence of decorative images had a small detrimental effect on comprehension. In the second study, participants read more difficult texts (low prior knowledge texts in multiple screens) and completed working memory and inhibitory ability tests. A significant interaction between comprehension and perceptual/attentional inhibitory ability was found: Participants with lower inhibitory capacity were affected by irrelevant pictures. In conclusion, evidence supported the hypothesis of a detrimental effect of irrelevant, decorative images on comprehension in e-learning, particularly for students with low attentional inhibition.